Bewegungsförderung im Bibliothekskontext – anhand des Fallbeispiels der Universitätsbibliothek Erlangen-Nürnberg - Heermann, Petra; Kolbe, Stephanie; Rohrwild, Jürgen; Scheuenstuhl, Klara (ABI-Technik, 2023)
Langes Sitzen – gängige Praxis bei Lernenden in wissenschaftlichen Bibliotheken – und allgemeiner Bewegungsmangel sind eine der Ursachen für Zivilisationskrankheiten. Neben Aufklärungsmaßnahmen können Arbeitsplätze mit ergonomischen Möbeln und Möglichkeiten für aktive Pausen hier Abhilfe schaffen. Im Folgenden stellen wir einen Ansatz an der Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU) vor, der mit Unterstützung des Projekts FAUbewegt die Situation schrittweise verbessern soll.<br
Keywords: Bibliothekseinrichtung; Ergonomie; Lernumgebung

The Research Data Management Organiser (RDMO) – a Strong Community Behind an Established Software for DMPs and Much More - Anders, Ivonne; Enke, Harry; Hausen, Daniela Adele; Henzen, Christin; Jagusch, Gerald; Lanza, Giacomo; Michaelis, Olaf; Peters-Von Gehlen, Karsten; Rathmann, Torsten; Rohrwild, Jürgen; Schönau, Sabine; Wedlich-Zachodin, Kerstin Vanessa; et al. (Data Science Journal, 2024)
This practice paper provides an overview of the Research Data Management Organiser (RDMO) software for data management planning and the RDMO community. It covers the background and history of RDMO as a funded project, its current status as a consortium and an open source software and provides insights into the organisation of the vibrant RDMO community. Furthermore, we introduce RDMO from a software developer’s perspective and outline, in detail, the current work in the different sub-working groups committed to developing DMP templates and related guidance materials.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Community building; Data management planning; DMP templates; DMP tool; Open source software